COMPARISION OF SELECTED FLAME AREA DETECTION METHODS IN VISION DIAGNOSTIC SYSTEM - Sawicki, Daniel; Kotyra, Andrzej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
This paper presents comparison edge detection method of combustion pulverized coal. Compared method are: Canny edge detection operator, level set method and Chan-Vese active contour method. Experimental results show that edges extracted with method based on Chan-Vese active contour model gives good result.